Genetic Screening for Melanocortin-4 Receptor Mutations in a Cohort of Italian Obese Patients: Description and Functional Characterization of a Novel Mutation - Santini, Ferruccio; Maffei, Margherita; Ceccarini, Giovanni; Pelosini, Caterina; Scartabelli, Giovanna; Rosellini, Veronica; Chiellini, Chiara; Marsili, Alessandro; Lisi, Simonetta; Tonacchera, Massimo; Agretti, Patrizia; Chiovato, Luca; et al. (The journal of clinical endocrinology and metabolism, 2004)
Mutations in the human melanocortin-4 receptor (MC4-R) gene may account for up to 5.8% of morbid nonsyndromic obesity. We have screened 120 unrelated obese patients for variants of the MC4-R gene. Four heterozygous missense variants were detected, including two polymorphisms (Val103Ile and Ile251Leu) previously described in the literature. A novel heterozygous mutation (Glu308Lys) was detected in a 36-yr-old female patient. Compared with the wild-type receptor, cells expressing the mutated receptor showed a reduced stimulation of cAMP production and a reduction of radioactive αMSH binding. No segregation of the mutation with the obese phenotype could be demonstrated. A second, potentially pathogenic mutation (Ser30Phe) was detected in a 31-yr-old female patient. Functional analysis of the mutated receptor showed no change in the affinity to the natural ligand αMSH nor limited ability to stimulate cAMP production. Sixty lean subjects were also screened, and no additional variants of the MC4-R gene were observed, except for two individuals with the Val103Ile polymorphism. In conclusion, we have screened a population of Italian obese subjects for MC4-R variants, demonstrating a 1.7% prevalence of potentially pathogenic mutations. A novel heterozygous missense mutation (Glu308Lys) that impairs MC4-R functional activity in vitro was characterized.